Literature listing. (December 2016) - Bates, Susan
Abstract: The quarterly Literature Listing is intended as a current awareness service for readers indicating newly published books, journal and conference articles on: patent search techniques, databases, analysis and classifications; patent searcher certification; patents relating to a) life sciences and pharmaceuticals and b) software; patent policy and strategic issues; trade marks; designs; domain names; and articles reviewing historical aspects of intellectual property or reviewing specific topics/persons. The current Literature Listing was compiled mid-August 2016. Key resources used are Scopus, Digital Commons, publishers' RSS feeds, and serendipity!